The Flint women's study: community perspectives on contraception and family planning, sexuality education and barriers to reproductive health. Issue 7 (1st July 2021) - Masten, Megan; Vega, Shayna; Hailemariam, Maji; Kagotho, Njeri; Key, Kent; Jefferson, Bernadel; Muhammad, Janice; Summers, Monicia; Spencer, Bryan; Sadler, Sharon; Robinson, DeWaun; Richie, Fallon; et al.
Abstract: Teenage pregnancy can have adverse social and health outcomes, and rates are high in Flint, Michigan as compared to the rest of the state and the USA. It is important to understand contributing factors to adolescent pregnancy to be able to better address this issue. This study examined qualitative data from interviews with 100 community members who participated in the Flint Women's Study, a study designed to better understand the hopes, dreams and needs of women in Flint, and their suggestions for how to address identified needs. Using a Community Based Participatory Approach, data were collected and analysed by a team of community members and academic researchers. The paper focuses on the theme of family planning among young women which included attitudes about contraception, sexuality education and bio-medical and structural barriers to accessing reproductive health. Community members emphasised the need for increased access to comprehensive contraception options, improved sexuality education in schools and from health care providers, and ultimately valuing young women.